2016
DOI: 10.1515/orhu-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Woodpecker – Common Starling interactions: a comparison of Old World and New World species and populations

Abstract: Woodpecker species whose cavities are most usurped by Common Starlings (Sturnus vulgaris) are widespread and generalists in their use of habitats. These include primarily woodpeckers that are similar in size to or slightly larger than the starling - such as the Great-spotted Woodpecker (Dendrocopos major) of Eurasia and the Northern Flicker (Colaptes auratus) and Red-bellied (Melanerpes carolinus) and Red-headed (M. erythrocephalus) Woodpeckers of North America. Usurpation occurs primarily in human-dominated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…Several studies in forests have found that nests situated closer to entrances are depredated more frequently (Czeszczewik and Walankiewicz 2003;Wesołowski and Rowiński 2012;Maziarz et al 2015). Other studies have reported similar nesting preferences in the Common Starling, finding that they selected deeper boxes with a larger bottom area and volume (Jackson and Jackson 2016), and with openings in the front wall (Flux and Flux 1981). Also, the studies of Perrins (1979), Lowther (2012), andLambrechts et al (2013) suggested that the House Sparrow also prefers medium and large nest boxes, especially with a large bottom area for roosting and nesting.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies in forests have found that nests situated closer to entrances are depredated more frequently (Czeszczewik and Walankiewicz 2003;Wesołowski and Rowiński 2012;Maziarz et al 2015). Other studies have reported similar nesting preferences in the Common Starling, finding that they selected deeper boxes with a larger bottom area and volume (Jackson and Jackson 2016), and with openings in the front wall (Flux and Flux 1981). Also, the studies of Perrins (1979), Lowther (2012), andLambrechts et al (2013) suggested that the House Sparrow also prefers medium and large nest boxes, especially with a large bottom area for roosting and nesting.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to other avian species that construct primary and secondary cavities, woodpeckers exhibit a distinct nesting behavior wherein they eschew the use of additional materials as nesting substrates, instead opting to deposit their eggs directly within the base of a burrow. According to Jackson et al [ 34 ], the presence of a limited quantity of wood debris at the base of the nest hole suggests that the softened wood debris also contributes to the brooding process within the nest hole. Multiple studies have indicated that the nesting behavior of woodpeckers, characterized by their brooding in nest holes, facilitates the colonization and flourishing of various fungi [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%